Counterfactual Thinking among University Students - et. al., Karrar Sahib Ibrahim Al Radhi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The importance of the research stems from the importance of its variables and the scarcity of Arab and local studies on them, and from the importance of the research sample - university students - who are considered among the most important segments of society, as the research community consisted of (23,353) students from the morning study for the academic year (2020-2021), As for the research sample, it consisted of (467) male and female students, with a percentage of (2%) from the research community, and to measure the research variables, the researcher prepared a measure of counterfactual thinking, and to identify the results of the research objectives, the researcher used the Statistical Analysis Package (SPSS), which showed a high level of Counterfactual thinking among university students, and based on the results reached, the researcher presented a set of conclusions and recommendations as well as proposals.